2019
DOI: 10.1159/000501363
|View full text |Cite
|
Sign up to set email alerts
|

Lung Cancer Presenting as Skin Metastasis of the Back and Hand: A Case Series and Literature Review

Abstract: Lung cancer has the highest mortality of all cancers in the United States. The incidence of lung cancer with metastases to the skin varies between 1–12%, with the highest incidence seen in men. Here, we present two cases of lung cancer presenting as skin metastasis. The first patient was an 80-year-old African American male who presented to the hospital for evaluation of a right upper back mass. A few months prior to admission, he was found to have a left lung mass on CT scan of the chest, he underwent biopsy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 15 publications
1
21
0
Order By: Relevance
“…Lung cancer is the most common one with skin metastasis. As in our patient, skin metastasis may be the first finding in the patients (7). The pathological definition of skin metastasis in patients is important in two aspects.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Lung cancer is the most common one with skin metastasis. As in our patient, skin metastasis may be the first finding in the patients (7). The pathological definition of skin metastasis in patients is important in two aspects.…”
Section: Discussionsupporting
confidence: 51%
“…Therefore in patients with a history of new developing skin lesions, especially in older patients, smokers and patients with a history of cancer in their families, histopathological diagnosis by taking a biopsy from the lesion is necessary to exclude the possibility of malignancy. Metastatic skin lesions are usually 1-3 cm in size and hard, painless, mobile lesions with normal skin color (7). Rarely, fruncle-like nodules, erosions, and ulcerated granuloma-like papules may occur (10)(11)(12).…”
Section: Discussionmentioning
confidence: 99%
“…Radiation therapy can be used if the chemotherapy is associated with severe pain or bleeding. 7,14 The patient in our case had a BRAF gene mutation; these mutations occur in 1-4% of NSCLC patients. 19,20 Non-V600E mutations are more likely to be observed in smokers than V600E mutations, which is consistent with previously reported results.…”
Section: Dovepressmentioning
confidence: 66%
“…[3][4][5] The frequencies of the different types of metastases are usually related to the frequency of the relative primary cancer, which varies according to age and sex. 6,7 The incidence of cutaneous metastasis increases with age and more so after the fifth decade of life. 4 Furthermore, the most common primary sites for males and females are the lungs and breast, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Sun et al reported that the type of adenocarcinoma was 3.4 times more frequent than that of SCC [2]. Skin metastases can appear on any cutaneous surface, and the most common sites are the chest, abdomen, head, and neck [3,4]. Cutaneous metastases have various manifestations, such as single papules/nodules or multiple lesions on anywhere of the skin, while other rare forms may show plaque-like lesions, erysipelas-like papules, zosteriform lesions, and scars [3,5].…”
Section: Introductionmentioning
confidence: 99%